Brackish water: an option for producing hydroponic Capsicum annuum in laminar flows of mineral nutrients (2018)
Sweet pepper plants were grown using a Nutrient Film Technique (NFT) hydroponic system. This study aimed to evaluate the effect of using brackish water on fruit production. The experiment was carried out in a randomized block design with seven treatments and five replications. The electrical conductivity of the water was 0.29, 1.39, 2.75, 4.49, 5.90, 6.76, and 7.09 dS m-1 in the treatments; this water was used for both the nutrient solution preparation and replenishment of crop evapotranspiration. The plant parameters: fruit diameter, fruit length, number of fruits per plant, mean fruit weight, total fruit weight per plant and fruit length/diameter ratio were evaluated 69 days after the transplanting. The use of brackish water with high electric conductivity values did not directly interfere with the sweet pepper production in NFT hydroponic systems, as long as these values did not exceed the sweet pepper salt tolerance of 1.5 to 1.8 dS m-1.